Optimal Coastal Land Use and Management in Krabi, Thailand: Compromise Programming Approach - Tipparat Pongthanapanich (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2006)
This paper identifies the optimal options of Krabis coastal land use to facilitate the final planning decision. Through compromise programming approach, the optimization models with respect to the weights assigned to two objectives of maximizing the net private and environmental benefits are formulated to derive the options. Various externality management scenarios based on different applications of policy tools are assessed. All scenarios suggest the optimal options in favour of mangrove conservation when both objectives are considered equally important. This is not the case when the private benefit objective is assigned a higher weight at a certain level for each scenario, which results in the pro development of shrimp farming. The policy framework based on a combination of carrying capacity and green taxation regime would ensure that even if the pro development option were chosen, the positive net environmental gain and the integrity of coastal receiving waters would be obtained.
Keywords: C61; D62; D74; Q22; Q24; 330; coastal land management; weighted compromise programming; decision making; Krabi province; Küstenregion; Aquakultur; Krebstiere; Umweltschutz; Mathematische Optimierung; Thailand